Peran Karakteristik Responden dan Dukungan Tenaga Kesehatan dalam Identifikasi Faktor yang Terkait dengan Kegagalan Pemberian ASI Eksklusif - Nur Hamidah; Kuntoro Kuntoro (Universitas Airlangga, 2016)
This study aims to identify the characteristics, factors support the role of health professionals and history place of birth of the respondents in the village Ngabab Pujon Malang. Type in this research was descriptive analytic study design. Samples from this study amounted to 72 respondents who have children aged 6–24 months was taken by simple random sampling, with a population of 144 respondents. Variables examined included the respondent characteristics such as age, education, and employment. While variable support role of health workers was a boosted in the form of exclusive breast-feed to the respondent when babies aged 0–6 months. For history variables place of birth that is the location where the respondent gave birth to her baby. The entire variable was measured using the enclosed questionnaire and analyzed using descriptive statistics. The result of this study is mostly mothers who are not exclusively breast-feeding are age 17–25 years which amounted to 35 (48.6%). The last education taken by the respondent is junior that is numbered 35 (48.6%). The majority of respondents worked, as many as 19 people (26.4%) worked as a farmer. Analysis of factors which support 51 health workers (70.8%) stated that health professionals do not support exclusive breast-feeding. For a history of childbed 36 people (50%) maternity midwife. The conclusion of this research is that the majority of respondents aged 19-25 years, working as a farmer, the last junior high school education does not provide exclusive breast-feeding, health professionals do not support exclusive breast-feeding. Health workers are expected to provide education and action to support exclusive breastfeeding.